PENGARUH PENGGUNAAN TEKNIK MIND MAPPING BERBASIS MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 2 NAN SABARIS - Emidar, Rika Adriyani, Irfani Basri, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research are (1) to describe writing ability level on exsposition text on the student SMP Negeri 2 Nan Sabaris grade VIII without using mind mapping technique as a base discovery learning model. (2) to describe writing ability on exsposition text on student SMP Negeri 2 Nan Sabaris grade VIII using mind mapping technique as a base discovery learning model in writing exposition text on the student SMP Negeri 2 Nan Sabaris grade VIII. Based on data analysis, mind mapping technique as a base discovery learning model have effect for writing ability level on exposition text on the student SMP Negeri 2 Nan Sabaris.Kata kunci: pengaruh, teknik mind mapping, model Discovery Learning, dan menulis, teks eksposisiÂ